Primary mucinous adenocarcinoma in a defunctionalized urinary bladder: a case report - Taneous, Mary (BioMed Central, 2009)
INTRODUCTION: Malignancies are rare in defunctionalized bladders and are thought to arise from metaplasia secondary to chronic inflammation. Transitional cell and squamous cell carcinomas are the most common but there are three reported cases of mucinous adenocarcinoma. CASE PRESENTATION: We report a 57-year-old Caucasian man presenting with penile discharge for 30 years following ileal conduit surgery for neurogenic bladder, and who was found to have primary mucinous adenocarcinoma of his defunctionalized bladder. CONCLUSION: Although urinary diversion without cystectomy is less common in current urologic practice, there are many patients with longstanding defunctionalized bladders. While there are no established surveillance protocols, defunctionalized bladder patients with urethral discharge should be evaluated.